Urban Functional Zone Mapping By Combining Multi-Source Social Sensing Data and Remote Sensing Imagery - (:unkn) unknown (My University, 2023)
Urban functional zones (UFZs) are regions with specific homogeneous urban functions. As the basic unit for urban environment research, updated UFZs mapping is essential for urban environmental research. However, the UFZs mapping is rarely available mainly because traditional urban environment inspection mainly focuses on land cover/land use from the single object level. With the increasing availability of Very High Resolution (VHR) remote sensing images and the emergence of social sensing geospatial big data, UFZs mapping became a prominent research field. It is necessary to provide a comprehensive view of UFZs mapping based on remote sensing research to evaluate the current status and provide guidance for future research. In this dissertation, a comprehensive review of UFZs mapping based on remote sensing research was summarized after synthesizing and summarizing the extant literature on UFZs research, thus to provide guidance for future research. Furthermore, a clear definition of UFZs was established to overcome the ambiguity definition issues, and according to the various functions of land in human life, a comprehensive category framework including nine types of UFZs was proposed. Guided by the inspiring brand new UFZs framework presented in the second chapter, land use based UFZ (impervious surface) was examined by integrating the remote sensing images and social sensing geospatial datasets. In the fourth chapter, the typical example of environment-related UFZs, brownfield sites were delineated by combining the multiple source data, including the NLCD dataset generated from remote sensing images, and social sensing geospatial datasets (e.g., Open Street Map land use polygons and geo-tagged tweets).Major contributions of this research can be summarized as follows. Firstly, it delineates a clear and distinct concept of Urban Functional Zones (UFZs) as homogenous functional regions, thereby addressing the concept ambiguity issue. Secondly, it introduces a novel, comprehensive categorization framework for UFZs, incorporating nine distinct types. This approach furnishes a transformative lens through which can utilized to perceive and analyze the urban environment. Lastly, this research employs the comprehensive UFZs framework to examine land-use UFZs (impervious surfaces), and environment related UFZs (brownfield sites) using multi-source geospatial data, inclusive of remote sensing imagery. This study not only refines the conceptual understanding of UFZs, but also presents a comprehensive framework to understand the urban environment from functional perspective.
Keywords: Brownfield sites; Impervious surface; Remote sensing; Social sensing; Urban functional zone